STARS, STORIES, AND RISK: HOW RATING REVIEWS AND ONLINE CUSTOMER REVIEWS DRIVE HOTEL BOOKING BEHAVIOR - Williams, Jason; Chandra , Clarine Eugenia; Palino , Patricia Putri; Chaerani , Fatimah Rezky; Hasim , Natalsjha Angelique Ersten Uno; Ardyan, Elia (International Journal of Economics, Business and Accounting Research (IJEBAR), 2025)
Online word of mouth (WOM) in the form of customer reviews is a crucial element in the consumer decision-making process, particularly in online hotel booking services. This study aims to analyze the influence of review ratings and online customer reviews on customer perceived risk and purchase decisions on the Tokopedia and Booking.com platforms. Furthermore, this study explores the role of customer perceived risk as a mediating variable between online WOM and purchase decisions. The method used is a quantitative approach by distributing questionnaires to 167 respondents who have experience booking hotels through both platforms. Data analysis was conducted using WarpPLS 8.0 software to test validity, reliability, and test the research hypotheses. The results show that review ratings have a positive and significant influence on purchase decisions and customer perceived risk. Meanwhile, online customer reviews have a positive and significant influence on purchase decisions, but their influence on customer perceived risk is not significant. Furthermore, customer perceived risk is proven to have a positive and significant influence on purchase decisions. These findings confirm that review ratings and risk perception are important determinants in consumer purchasing decisions in online hotel booking services.